2018
DOI: 10.1590/0074-02760170558
|View full text |Cite
|
Sign up to set email alerts
|

Detection of blaNDM-1 in Stenotrophomonas maltophilia isolated from Brazilian soil

Abstract: This study reports the presence of the bla NDM-1 gene in an isolate of Stenotrophomonas maltophilia obtained from a Brazilian soil, inside an IncA/C plasmid with ~ 45 Kb. To the best of our knowledge, this is the second report in the world and the first in Brazil of NDM-producing bacterium isolated from soil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 31 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Since the first description of blaNDM-1 gene in 2008 in Klebsiella pneumoniae (Yong, et al, 2009), several studies have reported the spread of this gene, with an increasing emphasis on the genus Acinetobacter spp. (Adams, et al, 2020, Chatterjee, et al, 2016, Dortet, et al, 2012, Fernández-Cuenca, et al, 2020, Furlan, et al,2018, Joshi,et al, 2017, Kumari, et al, 2021, Pagano, et al, 2015, Pasteran, et al, 2014, Pillonetto, et al, 2014, Poirel, et al, 2011, Rozales, et al, 2014, Tran, et al, 2017, Woodford, et al, 2006, Zhang, et al, 2013, Zhang, et al, 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first description of blaNDM-1 gene in 2008 in Klebsiella pneumoniae (Yong, et al, 2009), several studies have reported the spread of this gene, with an increasing emphasis on the genus Acinetobacter spp. (Adams, et al, 2020, Chatterjee, et al, 2016, Dortet, et al, 2012, Fernández-Cuenca, et al, 2020, Furlan, et al,2018, Joshi,et al, 2017, Kumari, et al, 2021, Pagano, et al, 2015, Pasteran, et al, 2014, Pillonetto, et al, 2014, Poirel, et al, 2011, Rozales, et al, 2014, Tran, et al, 2017, Woodford, et al, 2006, Zhang, et al, 2013, Zhang, et al, 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, sul1, sul2 and dfrA conferring resistance to SXT have been found chromosomally and in plasmids, and associated with Class 1 integrons and insertion sequence common region (ISCR) elements that enhance their mobility [2,54,55]. Likewise, other b-lactamase genes, such as bla CTX-M , bla NDM-1 , and bla IMP-8 have also been reported on plasmids in clinical and environmental Sma strains [35,[56][57][58][59].…”
Section: Acquired Molecular Mechanisms Of Resistancementioning
confidence: 99%
“…L1 is a Zn+ dependent β-lactamases which ensures that S. maltophilia is resistant to cephalosporines, carbapenem, penicillin's, and not monobactam, L2 however is an acid sensitive cephalosporine which confers resistance on S. maltophilia to cephalosporines, monobactam and penicillin 20 , 21 . Other mechanisms that have been reported in Stenotrophomonas species include plasmid borne resistant gene such as bla PER born on IncA/C Plasmid and bla NDM which conferred extended beta-lactam resistance on a strain of S. maltophilia isolated from the soil in Brazil 22 . Resistant mechanisms described above in Stenotrophomonas species might be due to the possession of extra-chromosomal genes acquired from other bacteria.…”
Section: Introductionmentioning
confidence: 99%